Resistance Training with Aerobic Active Recovery in Obesity and Metabolic Syndrome: Translational Rationale, Proposed Training Protocol, and Multi-Omics Research Framework—A Narrative Review - Karol Makiel; Agnieszka Suder (Journal of Clinical Medicine, 2026)
Background/Objectives: Resistance training with aerobic active recovery (RT-AR) is a proposed session architecture in which controlled low-impact aerobic activity replaces part of passive inter-set recovery. This hypothesis-driven narrative review evaluates its rationale in adults with obesity and metabolic syndrome (MetS) and proposes a multi-omics research framework. Methods: Structured searches of PubMed/MEDLINE and Scopus were combined with a narrative synthesis of systematic reviews, meta-analyses, controlled intervention studies, and mechanistic studies. Dedicated high-sensitivity searches were performed for studies directly evaluating aerobic active recovery during resistance-training inter-set recovery. Results: No randomized chronic intervention studies directly evaluating RT-AR in adults with obesity or MetS were identified; therefore, the rationale presented here is based on indirect evidence from conventional exercise and mechanistic studies. Evidence from overweight, abdominal-obesity, insulin-resistance, or type 2 diabetes cohorts was treated as partially applicable or indirect when the target phenotype differed. Aerobic, resistance, and combined training support improvements in body composition, cardiometabolic outcomes, physical function, and selected adipokines, whereas microbiota and DNA-methylation findings remain heterogeneous and are not RT-AR-specific. Conclusions: RT-AR should be regarded as a testable training architecture rather than an established therapeutic modality. Future trials should determine whether its effects exceed those attributable to total exercise dose, whether the resistance-training stimulus is preserved, and how diet, medication use, sex, and other major modifiers influence clinical and multi-omics responses.